The Utility of Lumbar Paraspinal Mapping in the Diagnosis of Lumbar Spinal Stenosis - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2009)
Objective: The aim of this prospective, blinded and controlled study is to evaluate the utility of lumbar paraspinal mapping in the diagnosis of lumbar spinal stenosis. Design: The subjects were assessed and allocated into three groups according to clinical and radiologic features with a standardized assessment protocol. These three groups were clinical and radiologic lumbar spinal stenosis, radiologic lumbar spinal stenosis, and the control group. The measurements of magnetic resonance imaging studies were performed by a blinded radiologist. An electromyographer who was masked to patients' data performed all the nerve conduction tests, lower-limb needle electromyography, and lumbar paraspinal mapping. The relations of clinical, radiologic, and electrophysiologic findings were investigated. Results: Sixty-two patients were enrolled in the study. Two patients were eliminated because electrophysiologic studies showed polyneuropathy. There were 28, 16, and 16 patients in clinical and radiologic lumbar spinal stenosis, radiologic lumbar spinal stenosis, and control groups, respectively. In the clinical and radiologic lumbar spinal stenosis group, the findings of limb needle electromyography were inconsistent with 50% acute and 46.4% chronic radiculopathy. However, the paraspinal mapping showed that there were fibrillation potentials and positive sharp waves in at least two levels in 92.8% of the patients in clinical and radiologic lumbar spinal stenosis. The mean total paraspinal mapping score was 33.64 +/- 21.17, which was significantly higher than the radiologic lumbar spinal stenosis and control groups. In the radiologic lumbar spinal stenosis group, the findings of paraspinal mapping were normal in 93.8% of the patients. Paraspinal mapping technique was found to be better correlated to the clinical findings than magnetic resonance imaging in asymptomatic patients. In the control group, 6 of 14 patients had high total paraspinal mapping scores (range, 0-9). Thosepatients with higher paraspinal mapping scores in the control group were mostly diagnosed with acute monoradiculopathy caused by disc herniation. Conclusions: Paraspinal mapping technique is a sensitive method in the diagnosis of lumbar spinal stenosis and reflects physiology of nerve roots better than the limb electromyography.
Keywords: Lumbar Spinal Stenosis; Paraspinal Mapping; Electromyography; Magnetic Resonance Imaging; ASYMPTOMATIC SUBJECTS; CLINICAL-EXPERIENCE; FOLLOW-UP; MUSCLES; ELECTROMYOGRAPHY; PREVALENCE; ADULTS